Korelasi Antara Body Shaming Dengan Mekanisme Koping Pada Remaja Di SMP - Asiah, Asiah; Safitri, Debby (Jurnal Kesehatan Mahardika, 2025)
Adolescence is marked by physical and psychological changes that can trigger body shaming, defined as ridicule toward a person’s physical appearance. This study aimed to examine the relationship between body shaming and coping mechanisms among students of SMPN 1 Pabuaran, Cirebon Regency. This correlational study employed a cross-sectional design with 73 respondents selected through proportional random sampling from a population of 265 students. The instruments used were the Body Shaming questionnaire and the Ways of Coping questionnaire. Data were analyzed using univariate and bivariate methods with the Chi-Square test. Results showed that 67% of respondents experienced moderate body shaming, and 79% used Emotion-Focused Coping. The Chi-Square test yielded a p-value of 0.030, indicating a significant relationship between body shaming and coping mechanisms. It is recommended to provide educational programs for adolescents to improve understanding and awareness, reduce body shaming practices, and promote the development of more adaptive coping strategies.